Reconstructing la Pieza del Despacho de Verano, the room of the Las Meninas: Problems and Possibilities - Thierry Rodolphe Greub (Philostrato, 2019)
The King’s summer study, la Pieza del Despacho de Verano, is a perfect point of departure for discussing the possibilities and limits of reconstructing a room in the Alcázar, the royal palace. Although the inventaries from 1666 and 1686 just tell us the subject and size of 33 pictures together with seven mirrors and six bufetes, the paper argues that it is possible to reconstruct the scale and decoration of the pieza del despacho de verano. On the basis of the order in the inventories, a convincing reconstruction is possible and leads to a visual presentation of the room that harbored Las Meninas. In a more general sense this gives us at hand a ‘layout’ for reconstructing other rooms in the king’s palace(s).